Pengaruh Fatwa Ulama Dayah dalam Masyarakat Aceh - Nurlaila Nurlaila; Zulihafnani Zulihafnani (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
Ulema (Islamic scholar) in Acehnese society occupies the same status as an elite community. Besides teaching religion, ulema also serve functions in various rituals of community life, such as praying for the deceased, reconciling disputes, helping the distribution of inheritance, and leading customary processions in the community. In Acehnese society, ulema not only lead and teach religion but also play a role in the political field. Aceh has Ulema Consultation Council (MPU) to decide on all religious matters. However, the community is more obedient to the ulema around them even though their fatwas are not in the MPU's decision. Sometimes their fatwas are different from the MPU’s. Since it is Tengku (Islamic scholar referred to in Aceh) in their network who decide, their opinions are obeyed. This article will examine how Teungku can influence the community in their network considering their fatwas do not have a binding power due to their unofficial status. This study was conducted using a qualitative approach. Some initial data information on the ulema network was obtained through study documentation in several districts in Aceh. The findings show that the fatwas of Tengku bind and the community obey their fatwas, for they are not aware of the Ulema Consultation Council. According to the community, MPU is absent and does not exist when needed. Furthermore, as an independent institution in deciding religious issues, MPU has not been socialized to the village level.